2003
DOI: 10.1590/s0100-83582003000100014
|View full text |Cite
|
Sign up to set email alerts
|

Mobilidade do sulfentrazone em Nitossolo Vermelho e em Neossolo Quartzarênico

Abstract: O objetivo deste trabalho foi determinar a mobilidade do herbicida sulfentrazone em duas classes de solos (Nitossolo Vermelho e Neossolo Quartzarênico), em função de índices pluviométricos crescentes, sendo, portanto, influenciado pelas propriedades químicas e físicas dos solos com diferentes teores de ferro. Em tubos de PVC de 10 cm de diâmetro por 50 cm de comprimento, preenchidos com os solos e saturados com água a 65% (p/p), foi aplicado o sulfentrazone (800 g ha-1). Na seqüência, foram simuladas chuvas di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…Sintomas da presença de resíduos de sulfentrazone foram observados na profundidade de 10 a 20 cm, apenas para o tratamento com aplicação em 2003/2004, na primeira coleta de solo, aos 467/24 DAA, respectivamente. Embora Rossi et al (2003) tenham avaliado em colunas de PVC a mobilidade do sulfentrazone em condições laboratoriais, os autores também constataram pequena mobilidade do herbicida em Nitossolo Vermelho (até 7,5 cm) e em Neossolo Quartzarênico (até 12,5 cm), mesmo quando submetidos a 90 mm de precipitação pluvial. Já segundo Benedito et al (1999), o sulfentrazone foi lixiviado para camadas de profundidade superior a 10 cm no perfil do solo, quando submetido à irrigação de 20 mm, 24 horas após a sua pulverização.…”
Section: Methodsunclassified
“…Sintomas da presença de resíduos de sulfentrazone foram observados na profundidade de 10 a 20 cm, apenas para o tratamento com aplicação em 2003/2004, na primeira coleta de solo, aos 467/24 DAA, respectivamente. Embora Rossi et al (2003) tenham avaliado em colunas de PVC a mobilidade do sulfentrazone em condições laboratoriais, os autores também constataram pequena mobilidade do herbicida em Nitossolo Vermelho (até 7,5 cm) e em Neossolo Quartzarênico (até 12,5 cm), mesmo quando submetidos a 90 mm de precipitação pluvial. Já segundo Benedito et al (1999), o sulfentrazone foi lixiviado para camadas de profundidade superior a 10 cm no perfil do solo, quando submetido à irrigação de 20 mm, 24 horas após a sua pulverização.…”
Section: Methodsunclassified
“…These data express the mobility of sulfentrazone is subject to many variables in field, however, it is understood that in general the sulfentrazone behavior can be mainly expressed by rainfall and soil physical characteristics in which is the herbicide. Also Rossi et al (2003) found that the mobility of sulfentrazone had different behavior between studied soil classes, because under a 90 mm rainfall, sulfentrazone reached 12.5 cm depth in columns with Typic Quartzipsamment, as observed and under the same rainfall, sulfentrazone reached 7.5 cm depth in columns with red nitosol. Although soil moisture content may change the distribution of sulfentrazone between the solution and sorbed phases, researchers showed that sulfentrazone dissipation also showed temperature dependency, which suggests that the halflife value for sulfentrazone at surface of tropical soils may be shorter (Martinez et al, 2010).…”
Section: Resultsmentioning
confidence: 51%
“…Rossi et al (2005b) observed that with increased saturation of the soil, there was an increase in the percolation of the product profile of a soil classified as Chernosol in which the herbicidal activity was observed through bioindicator plants to a depth of 17.5 cm under a rainfall of 90 mm. Studies conducted by Rossi et al (2003) found that the survival of sorghum plants in soil treated with sulfentrazone decreases with increased depth and increased as rainfall. It was observed a tendency to drag and accumulation of this herbicide in the soil profile as rainfall.…”
Section: Resultsmentioning
confidence: 99%
“…According to Liu et al (2010), in soils with little organic matter and little clay, the percolation of herbicides can occur, making them available Leaching of sulfentrazone in soils from the sugarcane region ... in the soil solution and making it amenable to transportation to the water table. Rossi et al (2003), working with columns and using an unstructured quartzarenic neosol, have detected poisoning by sulfentrazone in the indicator plants at 22.5 cm and 30 cm deep, respectively, for water depths of 60 and 90 mm. Therefore, it is assumed in this work that if water depth higher than 60 mm were applied, herbicide mobility would have been even greater.…”
Section: Resultsmentioning
confidence: 99%